REVERSE ENGINEERING ON RUBBER TRACK PAD FOR MEDIUM WEIGHT TANK - Hisyam Ramadhan, Muhammad
One of the important components of the defense system in NKRI are the usage of rubber track pad for medium weight tank. At the moment, the rubber track pad had to be imported. In this research, mechanical testing and physical testing will be performed to reverse engineer the imported rubber track pad. Mechanical testing included are tension testing, abrasion testing, and hardness testing. Physical testing included are swelling test, density testing, and aging test. The results will be compared with selected rubber Compounds based on its base rubber components that is compound A, compound B, compound C, and compound D. Compound A and B has synthetic rubber as its base. Compound C and D has natural rubber as its base. Testing results will also be compared with benchmark value that is the value of commercial rubber track pad. Mechanical and physical properties of the rubber track pad sample are relatively equal with the benchmark. The sample has higher value relative to the benchmark in specific gravity, 200% modulus, and hardness value. Conversely, the sample has lower value in tensile strength, abrasion resistance, and elongation compared to the benchmark. From comparison, compounds that will be used for further development of rubber track pad are compound with SBR (Ameripol 1502) as its base and compound with NR (SIR-20) as its base.